Provisional indicative world plan for agricultural development : a synthesis and analysis of factors relevant to world, regional and national agricultural development. Volume 1 - Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 1970)
The Food and Agriculture Organization Indicative World Plan (IWP) for agricultural development is an analysis of the major issues which are likely to be facing world agriculture in the 1970s and early 1980s. It is an attempt to provide a framework within which both the developing and the developed countries can better evaluate their particular agricultural production, trade, and resource development plans and
lje
Loans
Keywords: Agriculture and state